2014
DOI: 10.1007/s10384-014-0308-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of retinal nerve fiber layer thickness in patients with neurofibromatosis-1

Abstract: The results of our study suggest that RNFL thinning can be a helpful marker for the detection of OPGs in NF-1 patients. Larger studies with longitudinal data are required to confirm the role of OCT in the diagnosis and follow-up of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…The only reports have been on children with NF1-associated OPG where Chang et al and Topcu-Yilmaz et al found decreased pRNFL thickness 8,9 and Avery et al 20 demonstrated that most children with OPG and decreased RNFL thickness had visual acuity loss. All three studies found that pRNFL thickness values were equivalent between children with NF1 (without OPG) and healthy control subjects.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The only reports have been on children with NF1-associated OPG where Chang et al and Topcu-Yilmaz et al found decreased pRNFL thickness 8,9 and Avery et al 20 demonstrated that most children with OPG and decreased RNFL thickness had visual acuity loss. All three studies found that pRNFL thickness values were equivalent between children with NF1 (without OPG) and healthy control subjects.…”
Section: Discussionmentioning
confidence: 96%
“…3,24,25 This may explain the contrasting results regarding the thickness of RNFL and GCL-IPL in our study with respect to previous reports where thickness measurements between children with NF1 (and no OPG) and healthy controls were not significantly different. 8,9,20 Although generalized disease can have an important role in pathogenesis, the specific choroidal features and related retinal thickness aspects of NF1 also warrant consideration. In NF1, the choroid is altered because of the presence of characteristic nodules, 5,6,26,27 and reduction in mean choroidal thickness with generalized thinning of the neuroepithelium, photoreceptors together with the retinal pigment epithelium layer and the outer nuclear layer has been reported in adult patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…6) компьютерная периметрия -скотомы и секторальные выпадения; 7) оптическая когерентная томография -истончение слоя нервных волокон [3, 24,40].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified